Psychological Structure of Sociability in Uighur Nationality Representatives - K Yu Vdovina (Peoples' Friendship University of Russia (RUDN University), 2013)
The analysis of sociability of the Uighur nationality representatives is submitted in the article. The specific features of sociability as a personality property in the aspect of the ethnic background are revealed.